Rancang Bangun Sistem Informasi Bank Sampah di Desa Paguyangan - Lasmedi Afuan; Nofiyati Nofiyati; Nasichatul Umayah (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
Garbage is the residual material resulting from a production process, both industry and households. Based on Brebes district's statistical data, the Paguyangan sub-district is in fourth place with an average of 249.62 m3 of garbage per day. Paguyangan is one of the villages in the Paguyangan sub-district. Paguyangan has a garbage problem where people still have the habit of throwing garbage in the river and yards around the house. Based on this, the Paguyangan Village Hall plans to build a garbage bank to overcome the problem. A garbage bank managed activities such as recording savings transactions. This study conducted a web-based design of the Garbage Bank Information System (SIBS). SIBS is an information system used to help process garbage transactions at a garbage bank. The purpose of this SIBS is to facilitate officers and customers in processing services at the garbage bank. The methodology used in system development is the Waterfall method. SIBS development uses PHP as a programming language and MySql as the DBMS. The result of this research is a garbage bank information system. SIBS can be used in the management of garbage management transactions. Testing the system using Blackbox Testing and MOS. SIBS is easy to operate from the test results obtained.